2010
DOI: 10.1002/lsm.20889
|View full text |Cite
|
Sign up to set email alerts
|

A split‐face study of intense pulsed light on photoaging skin in Chinese population

Abstract: Background and Objectives: Intense pulsed light (IPL) is regarded as the gold standard of nonablative photorejuvenation. Yet there is still a need to observe its efficacy and safety on dark skin using a split-face module. Study Design/Materials and Methods: Twenty-four Chinese women with photoaging were enrolled in this study. Patients were randomized to receive four IPL treatments at 3-to 4-week intervals on one side of face, with the other side spared as control. Changes of photoaging were evaluated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…These effects can explain the improvement of photoaging. IPL is referred to as a safe modality for the treatment of photoaging skin in the Chinese population …”
Section: Discussionmentioning
confidence: 99%
“…These effects can explain the improvement of photoaging. IPL is referred to as a safe modality for the treatment of photoaging skin in the Chinese population …”
Section: Discussionmentioning
confidence: 99%
“…Particularly, IPL penetrates the skin more deeply than pulse dye laser and targets multiple chromophores at varying depths, including melanin and hemoglobin. Additional advantages of IPL include milder adverse reactions, general versatility, a higher skin coverage rate for lower cost and a shorter treatment duration because of the large area of application . Taub et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in treating ETR, the recovery of such degenerative dermal tissue is essential. For instance, Li et al17 reported that IPL treatment increases the content of dermal collagen and elastic fiber in a split-face study. The mechanism for this is selective absorption of light by tissue water leading to the conduction of heat to the surrounding collagen, resulting in subsequent collagen synthesis18.…”
Section: Discussionmentioning
confidence: 99%